PRE DIALYSIS CARE OF CHRONIC KIDNEY DISEASE PATIENTS AFFECTS MORTALITY OF THE DIALYSIS PATIENTS. - Anees, Muhammad; Hussain, Yasir; Mumtaz, Marium; al., et (Pakistan Journal of Kidney Diseases, 2021)
Introduction: The pre dialysis care affects mortality of the dialysis patients. So this study was conducted to determine the pre dialysis care and its effects on the mortality of the dialysis patients. Materials and methods: All patients who presented in nephrology out patients department and had indications for dialysis were included in study. Patients wereasked about details of chronic kidney disease diagnosis and management. They were inquired about dialysis, access knowledge and management of CKD complications on preformed questionnaire Pro forma. Results: One hundred and seventy six patients were enrolled in the study and were followed up to one year. Only small number of patients 2 (1.1%) were under care of nephrologist when they were diagnosed of CKD while rest of the patients were getting treatment from non-renal physicians like urologists, medical specialists and general practitioners. Most of the patients 155 (88.1%) were anemic (Hb < 11 G/dL) and large number of patients 67 (38.1%) were on blood transfusions for anemia treatment. Dialysis was initiated through temporary catheter in 155 (88.1%) patients. Overall mortality was 78 (55.3 %) after a year and maximum 58 (40.1%) was in initial three months. Conclusion: This study shows that majority of the patients were not getting pre-dialysis care according to international guidelines. These patients were being managed by nonrenal physicians. Poor quality of pre dialysis care leads to high mortality of the dialysis patients.